Enabling n-type polycrystalline Ge junctionless FinFET of low thermal budget by in situ doping of channel and visible pulsed laser annealing - Huang, Wen-Hsien; Shieh, Jia-Min; Kao, Ming-Hsuan; Shen, Chang-Hong; Huang, Tzu-En; Wang, Hsing-Hsiang; Yang, Chih-Chao; Hsieh, Tung-Ying; Hsieh, Jin-Long; Yu, Peichen; Yeh, Wen-Kuan (My University, 2017)
A low-thermal-budget n-type polycrystalline Ge (poly-Ge) channel that was prepared by plasma in-situ-doped nanocrystalline Ge (nc-Ge) and visible pulsed laser annealing exhibits a high electrically active concentration of 2 x 10(19) cm(-3) and a narrow Raman FWHM of 3.9 cm(-1). Furthermore, the fabricated n-type poly-Ge junctionless FinFET (JL-FinFET) shows an I-on/I-off ratio of 6 x 10(4), V-th of % -0.3 V, and a subthreshold swing of 237mV/dec at V-d of 1V and DIBL of 101mV/V. The poly-Ge JL-FinFET with a high-aspect-ratio fin channel is less sensitive to V-th roll-off and subthreshold-swing degradation as the gate length is scaled down to 50 nm. This low-thermal-budget JL-FinFET can be integrated into three-dimensional sequential-layer integration and flexible electronics. (C) 2017 The Japan Society of Applied Physics